Religious Moderation Within the Frame of Tolerance: Islamic Studies and Diversity in Central Kalimantan - Siti Khodijah; Surawan Surawan; Fajariah Fajariah (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2025)
This article discusses the importance of exploring the concept and implementation of religious moderation, focusing on the understanding of Islam and local perspectives in Central Kalimantan. The results of this research emphasize the significance of tolerance in a diverse religious community in the region, particularly in maintaining harmony and preventing conflicts. Additionally, the study delves into strategies to strengthen religious moderation, encompassing areas such as education, inter-religious dialogue, character formation, and reinforcing religious-cultural relations. The analysis of Islam and the dynamics of the times involves understanding the essential values of Islam, responses to social changes, and the role of the younger generation in the current context. The research contributes to harmony and the prevention of extremism through in-depth understanding, changes in values, and social empowerment, forming a more holistic vision that supports religious harmony in the diverse and dynamic society of Central Kalimantan.